Pharmacogenomics & its Application in Ophthalmology - Surabhi Gupta; Sanjiv Kumar; Prafful Garg (Delhi Journal of Ophthalmology)
Drug reactions in some individuals may be qualitatively different from the effects usually observed in the majority of subjects. The mechanisms underlying such unusual responses to drugs have been shown to be of genetic origin. Pharmacogenetic variations in drug responses maybe seen in various conditions including cancer and some heart diseases. Pharmacogenomics makes use of the genome of an individual so as to choose a particular drug therapy for responders only and avoiding it in non-responders i.e. tailoring the drug therapy based on the individual's genotype. However this field is still in its infancy since multiple genes, environmental factors and multiple single nucleotide polymorphisms may also contribute to a disease. Also, ethical, legal and social issues add to the limitations. At present its application in ophthalmology is in experimental stage and researches are ongoing to find genetic basis of altered drug responses in ocular diseases. This article briefly elucidates pharmacogenomic basis of variation in drug responses in two ocular diseases glaucoma and age related macular degeneration.